1996
DOI: 10.1002/pro.5560050907
|View full text |Cite
|
Sign up to set email alerts
|

An optimized g‐tensor for rhodobacter capsulatus cytochrome c2 in solution: A structural comparison of the reduced and oxidized states

Abstract: The optimized g-tensor parameters for the oxidized form of Rhodobacter capsulatus cytochrome c2 in solution were obtained using a set (50) of backbone amide protons. Dipolar shifts for more than 500 individual protons of R.capsularus cytochrome c2 have been calculated by using the optimized g-tensor and the X-ray crystallographic coordinates of the reduced form of R. capsulatus cytochrome c2. The calculated results for dipolar shifts are compared with the observed paramagnetic shifts. The calculated and the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…This suggests that hindrance to rotation for the aromatic group of Phe98 in the oxidized protein is caused by the b protons of Lys12 and the side-chain protons of Leu100, which are apparently closer to the phenyl group of Phe98. This is consistent with the redox-related conformation studies, which have shown that Asn11, Lys12, Lys99, and Leu100 experience significant local conformational changes with a change in oxidation statẽ Zhao et al, 1996!. The increased constraints on Phe98 in the oxidized cytochrome are surprising because Phe98 is in the hinge region~positions 88-102, Dumortier et al, 1998!, which rotates away from the heme ;30 time0s.…”
Section: Noe Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…This suggests that hindrance to rotation for the aromatic group of Phe98 in the oxidized protein is caused by the b protons of Lys12 and the side-chain protons of Leu100, which are apparently closer to the phenyl group of Phe98. This is consistent with the redox-related conformation studies, which have shown that Asn11, Lys12, Lys99, and Leu100 experience significant local conformational changes with a change in oxidation statẽ Zhao et al, 1996!. The increased constraints on Phe98 in the oxidized cytochrome are surprising because Phe98 is in the hinge region~positions 88-102, Dumortier et al, 1998!, which rotates away from the heme ;30 time0s.…”
Section: Noe Analysissupporting
confidence: 84%
“…The assignment of ferricytochrome c 2 provides a basis for comparison of the oxidized and reduced solution structures and determination of the pseudo-contact shifts~Williams Feng et al, 1990a;Gao et al, 1991;Turner & Williams, 1993;Zhao et al, 1996! resulting from the presence of the paramagnetic iron in the oxidized cytochrome c 2 .…”
mentioning
confidence: 99%
“…Similar to the changes of heme propionate observed in eukaryotes, cyts c 2 ( 160 , 239 242 ) and c 6 ( 220 , 243 , 244 ) from some prokaryotes also display conformational changes in the heme propionate between the reduced and oxidized states of the protein. In the cases of cyt c H (reduces methanol oxidase in methylotropic bacteria) from Methylobacterium extorquens and cyt c 552 ( 245 247 ) (electron donor to a ba 3 –cytochrome c oxidase) from T. thermophilus , there is no conserved water molecule in the heme pocket, suggesting that the water-mediated H-bonding network is not a critical requirement for ET.…”
Section: Cytochromes In Electron Transfer Processesmentioning
confidence: 57%
“…The nuclei in these residues should experience intermolecular pseudocontact shifts in the oxidized complex because the Fe(III) is paramagnetic (spin = 1/2). Pseudocontact shifts have been exploited before for determination of the orientation of the magnetic susceptibility tensor and in structural studies [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. While the present work was in progress, the use of intermolecular pseudocontact shifts was reported in a study of the complex of ferricytochrome b 5 -ferricytochrome c [48].…”
Section: Effects Of Complex Formationmentioning
confidence: 96%
“…The cytochrome f:plastocyanin ratio was 0.8. Structure haem proteins, however, χ zz is oriented nearly perpendicular to the haem plane [35][36][37][38][39][40][41][42][43][44][45][46][47][48], making a small angle with the bond between the iron and the sixth ligand. It was therefore assumed that χ zz in cytochrome f is oriented along the bond between the iron and the N-terminal amino group.…”
Section: Pseudocontact Restraintsmentioning
confidence: 99%